2017
DOI: 10.1016/j.ypmed.2016.11.027
|View full text |Cite
|
Sign up to set email alerts
|

Global participation in sport and leisure-time physical activities: A systematic review and meta-analysis

Abstract: This review aimed to determine the most popular physical activities performed by children, adolescents, and adults globally. Statistic bureau websites and article databases Scopus, ProQuest, SPORTDiscus, and Science Direct were searched between November 17th, 2014 and April 31st, 2015. Eligible studies were published in the last 10years with participation rates for specific physical activities among individuals five years or older. Data extraction for included articles (n=64) was assessed independently and agr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
273
0
13

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 421 publications
(332 citation statements)
references
References 56 publications
7
273
0
13
Order By: Relevance
“…Also Hulteen et al. concluded that soccer was the most popular activity for boys. However, the girls in our study also expressed a high preference for soccer and it should not be viewed as just an activity for boys.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also Hulteen et al. concluded that soccer was the most popular activity for boys. However, the girls in our study also expressed a high preference for soccer and it should not be viewed as just an activity for boys.…”
Section: Discussionmentioning
confidence: 99%
“…Schools provide an ideal setting for these interventions and are in a unique position to contribute to the recommended minimum of 60 minutes of daily PA for children . In addition, many of the barriers for children's leisure‐time PA, including their parent's socioeconomic status, parental support for active modes of travel, such as cycling, and the cost of sporting activities, do not apply in the school setting . Numerous efforts have been made to intervene and increase children's PA levels in school .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, sport was created by men and for men (Hargreaves, ), but women are now participating, and exercising, in record numbers (Hulteen et al., ). Pushing cultural and physical barriers, they are training hard, achieving personal bests and enjoying the everyday physical and social pleasures of a wide range of movement cultures.…”
Section: Introductionmentioning
confidence: 99%
“…However, according to the report from the National Health Survey conducted in 2014‐2015, only 57.7% of Australian men and 53.3% of Australian women met the WHO Physical Activity Guidelines . Recreational running, which may also be referred to as jogging, is one of the most common physical activities worldwide, with regular running consistently shown to reduce all‐cause and cardiovascular mortality risks . In Australia, the rate of participation in running increased from 4.3% in 2005‐06 to 7.4% in 2013‐14 .…”
Section: Introductionmentioning
confidence: 99%